The Effects of Hand and Foot Training Videos on Family Caregivers' Knowledge, Attitude, and Behavior in Training Post-Stroke Patients at RSUD Goeteng Taroenadibrata - Ade Sinta Oktaviana; Sodikin (UM Purwokerto Press, 2026)
Family caregivers play a critical role in the rehabilitation of post-stroke patients, especially in performing physical exercises such as Range of Motion (ROM) exercises. This study aimed to evaluate the effect of a video training intervention on family caregivers’ knowledge, attitude, and behavior in training post-stroke patients. A pre-experimental one-group pre-test post-test design was employed. Family caregivers of post-stroke patients at RSUD Goeteng Taroenadibrata participated in the study. Data was collected through pre- and post-test questionnaires that assessed caregivers' knowledge, attitude, and behavior regarding stroke rehabilitation exercises. The Wilcoxon signed-rank test was used for statistical analysis. The results indicated significant improvements in the caregivers' knowledge, attitude, and behavior after watching the training video, with p-values of 0.000 for all variables, indicating a strong positive effect. Video-based educational interventions are effective in enhancing the knowledge, attitude, and behavior of family caregivers in training post-stroke patients. This approach can be recommended as a cost-effective method to improve caregiver involvement in post-stroke rehabilitation.